An update on biologic treatments for neuromyelitis optica spectrum disorder. (2nd January 2023) - Kim, Woojun; Kim, Ho Jin
ABSTRACT: Introduction: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease of the central nervous system mediated by antibodies targeting the aquaporin-4 (AQP4) water channel expressed on astrocytes. The binding of specific antibodies to AQP4 causes complement-dependent cytotoxicity, leading to inflammation and demyelination. Several recent phase 2 and 3 randomized placebo-controlled trials showed the efficacy and safety of monoclonal antibody therapies targeting B-cells, interleukin-6 receptor, and complement. Areas covered: Current biologic treatments for NMOSD and developments therein, and unresolved issues in NMOSD treatment. Expert opinion: New biologic treatments demonstrate high efficacy and good safety for patients with AQP4-IgG-positive NMOSD. The optimal therapeutics for seronegative NMOSD, pediatric patients, and female patients who are pregnant or wish to be are unclear, and further research is needed. Also, real-world studies of new biological agents and the data on the durability of their beneficial effects and their long-term safety are required. Effective rescue therapy for an acute attack is critical given permanent disability in NMOSD is attack-related, and biologic agents that treat acute attack are emerging. If such treatments are to become widely applied, studies on the most cost-effective treatment strategies are needed.